Tautiškosios religinės tapatybės svarstymai literatūros teologijos aspektu - Čiočytė, Dalia (Literatūra, 2015)
The article sets to explore the theoretical principles of literary theology which is employed to discuss and interpret the works by Vincas Mykolaitis-Putinas – the classic writer of Lithuanian literature. It is assumed that several Putinas’ works represent different forms of Lithuanian religious identity: traditional Western Christianity and modern individualism. The latter is being interpreted in the context of the deistic notion of God. A hypothesis is being made that some strong emphases on such aspects of Lithuanian Christianity as the fear of God may have been influenced by the emergence of the deistic and atheistic concepts of the Deity.